DAYA GUNA TRAMADOL 1 MG/KGBB DIBANDING PETIDIN 0,5 MG/KGBB YANG DIBERIKAN DRIP INTRAVENA SELAMA 10 MENIT UNTUK MENCEGAH MENGGIGIL PADA PASIEN SEKSIO SESARIA DENGAN ANESTESI SPINAL - , Kamala Kan Nur Azza, Dr. Yusmein Uyun, Sp.An, KAO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bacground and objective: The incidence of shivering in patients during Caesarean section under spinal anesthesia is between 39% - 85%. Shivering is very uncomfortable and aggravates postoperative pain. In addition to discomfort, severe shivering may be associated with a marked rise in oxygen consumption leading to an increased stress on the circulatory and respiratory systems and also increase in intraocular and intracranial pressures. Drug of choice for prevention and treatment of this complication is pethidin 25 mg iv (0.4-0.5 mgkg-1) but has still many side effects such as nausea and vomiting, respiratory depression and itching. An alternative drug, tramadol 1 mgkg-1 iv can be expected to prevent the spinal anasthetic shivering effectively and has a few complications. The aim of this study is to compare the efficacy of tramadol 1 mgkg-1 dripped intravenously over 10 minutes versus pethidin 0.5 mgkg-1to prevent shivering in obstetric patients during cesarean section under spinal anesthesia. Method: The design of this study is a double blind randomized controlled clinical trial (RCT) parallel design. Seventy six patients whom underwent caesarean section (physical status ASA I or II according to ASA classification) were divided equally into: Group T (Tramadol) and Group P(Pethidin). The number of patients in each group was 38 patients. Before injection of spinal anesthetic drug, patient in group T and group P received tramadol 1 mgkg-1and pethidin 0.5 mgkg-1 intravenous drip over 10 minutes respectively. Data were statistically analyzed with independent t, Mann Whitney U, Chi-square, Spearman Correlation and Lamda test. P value of <0.05 was declared a significant result with 95% level of confidence. The measurement of outcomes were based on shivering rate and side effects of the drugs. Result :The incidences of shivering were reported in 8 patients in group P (21.1%) and 1 patient in group T (2.6%). The statistical analysis showed significant difference (p<0.05) between the two groups. The secondary outcome showed incidences of nausea and pruritus. Nausea was reported in 4 patients in group P (10.5%) and 3 patients in group T (7.9%) (p> 0.05) and itching was reported in 8 patients in group P (2.1%) and no incidence of itching in group T (p<0.05). Conclusion : Tramadol 1 mgkg-1 over 10 minutes intravenous drip is more efficient than pethidin 0,5 mgkg-1in preventing shivering in patients during caesarean section under spinal anesthesia.